PENGARUH PENAMBAHAN ABU SEKAM PADI PADA PEMBUATAN BATU BATA TERHADAP KUAT TEKANNYA - Ayat, Matsyuri (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2020)
The use of bricks in the world of construction, both as structural and non-structural elements, cannot be replaced. This can be seen from the many construction projects that use bricks as walls in building and housing construction, fences, channels, and foundations. Bricks are made from a mixture of soil and water. In this study, the process of making bricks will be tried to mix the soil with the additional material of rice husk ash to determine the effect of changes in the mechanical properties of the bricks in terms of the shrinkage test and compressive strength test. The soil sample used is a type of clay soil originating from Suakarsa Village, Teluk Gelam District, Ogan Komering Ilir Regency. This study used a sample of block-shaped bricks with a length of 19.5 cm, a width of 9.5 cm, and a height of 9 cm. The variations in the composition of rice husk ash added were 0%, 3%, 4%, 5% and 6%. The addition of rice husk ash with a composition percentage of 3% to 6% can affect the mechanical properties of the bricks, namely reducing burnt losses and increasing the compressive strength of the bricks. The minimum burn value was achieved in the percentage of rice husk ash with a variation of 6%, namely by 37.55% burn loss. The optimum compressive strength value is achieved in the percentage of rice husk ash with a variation of 3% with 14 days of age, the compressive strength value is 76.88 Kg / cm². Key Words : Bricks, Rice Husk Ash, Compressive Strength.